Modulating motility of intracellular vesicles in cortical neurons with nanomagnetic forces on-chip. Issue 5 (6th February 2017) - Kunze, Anja; Murray, Coleman Tylor; Godzich, Chanya; Lin, Jonathan; Owsley, Keegan; Tay, Andy; Di Carlo, Dino
Abstract : On-chip modulation of cell internal vesicle motion pattern. Abstract : Vesicle transport is a major underlying mechanism of cell communication. Inhibiting vesicle transport in brain cells results in blockage of neuronal signals, even in intact neuronal networks. Modulating intracellular vesicle transport can have a huge impact on the development of new neurotherapeutic concepts, but only if we can specifically interfere with intracellular transport patterns. Here, we propose to modulate motion of intracellular lipid vesicles in rat cortical neurons based on exogenously bioconjugated and cell internalized superparamagnetic iron oxide nanoparticles (SPIONs) within microengineered magnetic gradients on-chip. Upon application of 6–126 pN on intracellular vesicles in neuronal cells, we explored how the magnetic force stimulus impacts the motion pattern of vesicles at various intracellular locations without modulating the entire cell morphology. Altering vesicle dynamics was quantified using, mean square displacement, a caging diameter and the total traveled distance. We observed a de-acceleration of intercellular vesicle motility, while applying nanomagnetic forces to cultured neurons with SPIONs, which can be explained by a decrease in motility due to opposing magnetic force direction. Ultimately, using nanomagnetic forces inside neurons may permit us to stop the mis-sorting of intracellular organelles, proteins and cell signals, which have been associated with cellular dysfunction. Furthermore, nanomagnetic force applications will allow us to wirelessly guide axons and dendrites by exogenously using permanent magnetic field gradients.